Denominational inflation: Limited currency divisibility in cash payment systems – Tanzania as a case study - Francis Stephen Nyonzo (Advanced Research in Economics and Business Strategy Journal)
This study examines the impact of the limited divisibility of money on price setting and inflation in Tanzania, a country that relies heavily on cash transactions. Through analyzing bus fares and prices listed in both domestic and international online shopping platforms, the research highlights the economic implications of rounding prices to the nearest available currency denomination due to the absence of small denominations. The analysis reveals that ordinary bus users pay more due to price rounding to the nearest available denominations. Digital payment systems, on the other hand, reduce the need for adjustments that inflate costs. The study employed logistic regression to examine the relationship between the last digit of the price and the two different shopping malls. The findings suggest promoting digital payment systems to enhance the effectiveness of monetary policy, reduce transaction costs, and ensure price accuracy, thereby proposing policy directions for Tanzania to transition from cash-based to digital payment systems.